(untitled) (World Science, 2022)
Structural, optical and electronic properties and elastic constants of Cd1-x-yZnx HgyTe alloys have been studied by employing the commercial code Castep based on density functional theory. The generalized gradient approximation and local density approximation were utilized as exchange correlation. Using elastic constants for compounds, bulk modulus, band gap, Fermi energy and Kramers–Kronig relations, dielectric constants and the refractive index have been found through calculations. Apart from these, X-ray measurements revealed elastic constants and Vegard’s law. It is seen that results obtained from theory and experiments are all in agreement.